Evaluasi Status Bahan Organik Dan Sifat Fisik Tanah (Bulk Density, Tekstur, Suhu Tanah) Pada Lahan Tanaman Kopi (Coffea Sp.) di Beberapa Kecamatan Kabupaten Dairi - Emalia Sinarta Br.Tarigan; Hardy Guchi; Posma Marbun (Universitas Sumatera Utara, 2015)
Evaluation Status of Organic Matter Content and Soil Physical Properties (Bulk Density, Texture and Soil Temperature) the Coffee Crop Land (Coffeea Sp.) in Some Districts Dairipurpose to makeevaluation status of the organic matter and soil physical properties (bulk density, texture and soil temperature) the coffee crop land (Coffeea Sp.) in some districts Dairi. Sampling using free methods tosurvey the level of review and analysis of data C- organic by Walkey and Black method, bulk densityby Ring Sample method, texture by Hydrometer method and soil temperature (oC) using the formula ofBraak, and interpret the nutrient status of the map through the program ArcMap 10. Parameters in the analysis are C-organik, bulk density, texture and soil temperature. The result of research showed thatthe nutrient status of the research area map C-organic consists of a very low criteria (3 sample), low(13 sample),being(12 sample) danhigh (10 sample). Bulk Density, porous criteria (13 sample) and solid (25 sample). Texture, very smoothcriteria (1 sample), smooth (6 sample), rather smooth (10 sample), being (9 sample), a bit rough (7 sample) dan rough (4 sample), andrezim Soil TemperatureIsohyperthermic (38 sample). Keywords :C-organic, bulk density, texture and soil temperature.